Liberalization and Financial Crisis in Uruguay (1974-1987) - Leone, Alfredo (IMF Working Papers; Working Paper ;, 1991)
The financial system in Uruguay underwent a serious crisis beginning in 1982, which resulted in the failure of many banks and to a major restructuring of the financial system. This paper examines the causes and consequences of this crisis, exploring the relationship between developments in the financial sector and those in the rest of the economy. It also discusses the effect of financial liberalization, and government policies in banking regulation and supervision on the crisis, as well as the measures that the government took to deal with the crisis.